2014
DOI: 10.1155/2014/394264
|View full text |Cite
|
Sign up to set email alerts
|

Nanotechnology-Applied Curcumin for Different Diseases Therapy

Abstract: Curcumin is a lipophilic molecule with an active ingredient in the herbal remedy and dietary spice turmeric. It is used by different folks for treatment of many diseases. Recent studies have discussed poor bioavailability of curcumin because of poor absorption, rapid metabolism, and rapid systemic elimination. Nanotechnology is an emerging field that is potentially changing the way we can treat diseases through drug delivery with curcumin. The recent investigations established several approaches to improve the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
136
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 235 publications
(144 citation statements)
references
References 133 publications
2
136
0
6
Order By: Relevance
“…Any compound, irrespective of its solubility, can be entrapped inside a liposome, resulting in a slow degradation during transport to the target, minimal side-effects and greater stability (Ghalandarlaki et al 2014).…”
Section: Liposomal Systems As Carriers For Bioactive Compoundsmentioning
confidence: 99%
“…Any compound, irrespective of its solubility, can be entrapped inside a liposome, resulting in a slow degradation during transport to the target, minimal side-effects and greater stability (Ghalandarlaki et al 2014).…”
Section: Liposomal Systems As Carriers For Bioactive Compoundsmentioning
confidence: 99%
“…However, a poor solubility of curcumin in water at physiological pH and low bioavailability limited the absorption of curcumin after administration (Jäger et al, 2014;Siviero et al, 2015). To overcome the problems of poor solubility and low bioavailability, recently several nanotechnology approaches have been reported for the encapsulation of curcumin into nanoparticles such as liposomes, polymeric nanoparticles, micelles, nanogels, cyclodextrins, dendrimers, silvers and solid lipids as one of the useful alternatives (Ghalandarlaki et al, 2014). Although these biocompatible nanocarriers hold a promise to enhance the bioavailability and deliver therapeutic concentrations of curcumin the safety and toxicity issues cannot be ignored.…”
Section: Introductionmentioning
confidence: 99%
“…Curcumin, a plant polyphenol extracted from the turmeric rhizome, possesses antioxidant, anticoagulant, anti-inflammatory, anti-atherosclerotic, lipid-lowering and anti-aging properties (9,10). Previous studies have demonstrated that curcumin is a highly effective anticancer agent (10,11).…”
Section: Introductionmentioning
confidence: 99%